KAJIAN HUKUM ISLAM DAN HUKUM ADAT PADA KEWARISAN ANAK ANGKAT DI DESA WATESTANJUNG KECAMATAN WRINGINANOM KABUPATEN GRESIK - Muhamad Maulana Hadziqunnuha Arrozi; Suprapto (Journal of Islamic Shariah and Research Applications, 2026)
The distribution of inheritance to adopted children is very important, knowing that adopted children are not entitled to inheritance because the appointment of children does not bring legal consequences in terms of blood relations, guardianship relationships and inheritance relationships. Therefore, the author is interested in conducting research on the provisions of inheritance for adopted children from the perspective of Islamic law and customary law. This research aims to find out how the provisions of Islamic law and customary law on the inheritance of adopted children and to find out how the practice of inheritance of adopted children in Watestanjung Village, Wringinanom Subdistrict, Gresik Regency. This research includes descriptive research aimed at obtaining information about several conditions and explaining and describing the results of research conducted in the research environment. To obtain the necessary data the author uses primary data and secondary data. The primary data included the Head of Lurah along with local officials and the community, secondary data in this study is about historical and geographical. Based on the research conducted, the following results and conclusions were obtained: a. Lack of legal counseling, both by the local government and from community organizations. b. Blurring of the child's identity which resulted in some members of the community not knowing that Munadifah was actually an adopted child (younger generation), and caused social jealousy in the family.